Using remarkability to define coastal flooding thresholds - Frances C. Moore (Nature Portfolio, 2020)
The degree of flooding in a particular location depends sensitively on local topography and bathymetry. Here the authors used the remarkability of flood events to estimate county-specific flood thresholds for shoreline counties along the Atlantic and Gulf coasts of the United States and found that several areas experience noticeable flooding at a height lower than existing thresholds.